2012
DOI: 10.1590/s1807-25772012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Profile and scientific production of Brazilian researchers in oral pathology

Abstract: OBJECTIVE: This study evaluated the profile and scientific production of researchers in oral pathology who received grants in the area of Dentistry from the Brazilian National Research and Development Council. MATERIAL AND METHOD : The standardized online curriculum vitae (Curriculum Lattes) of 34 researchers in oral pathology who received grants in the years 2008-2010 were analyzed. The variables were: gender, affiliation, time from completion of the PhD program, scientific production, and supervision of unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
4
2
Order By: Relevance
“…However, the findings of this study that indicate that the majority (92.8%) of nursing PQ researchers are female are in contrast with the results of other studies that found a male predominance among PQ/CNPq researchers of other fields of knowledge, for instance, those which found 72.7% of male PQ researchers in cardiology (9) , 68% in medicine (10) , 70.6% in oral pathology (11) , and 74% in neuroscience (12) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the findings of this study that indicate that the majority (92.8%) of nursing PQ researchers are female are in contrast with the results of other studies that found a male predominance among PQ/CNPq researchers of other fields of knowledge, for instance, those which found 72.7% of male PQ researchers in cardiology (9) , 68% in medicine (10) , 70.6% in oral pathology (11) , and 74% in neuroscience (12) .…”
Section: Discussioncontrasting
confidence: 99%
“…But this is not a reality only for nursing. Studies on other fields of knowledge also show this concentration in São Paulo and in the Southeast region (9)(10)(11)(12) . It should be noted that the spatial concentration of scientific production is not a Brazilian peculiarity, instead, it has been a growing tendency in the contemporary world.…”
Section: Discussionmentioning
confidence: 88%
“…Feminization is also notable in the body of Doctorate and Master's Degree students of the courses of this field of knowledge (17) . However, this predominance of women in the Pq universe of Collective Health contrasts with the results of other studies that show a greater presence of men among Pq professors in other areas of knowledge (18)(19)(20)(21)(22)(23) . CNPq data indicate that in 2002 there were 0.84 women registered in the Directory of Research Groups for each man, and that ratio decreased greatly in the grant of productivity scholarship.…”
Section: Discussioncontrasting
confidence: 99%
“…The productivity differentials related to professor training are consistent with studies that suggest a positive relationship between Graduate professor training and scientific productivity (36) . The productivity differentials related to the institutional affiliation of the professor revealed in this study reinforce the spatial and institutional concentration of Brazilian scientific production, an issue that is widely highlighted in other studies (18)(19)(20)(21)(22)(23) . Studies point to two sets of factors that contribute to this heterogeneity/differentials: The unobservable factors related to the ability and motivation of the scientist to produce and the observable factors related to gender, origin, training and other institutional conditions (34,38) .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation